Developing a research community within an online healthcare feedback platform. (20th January 2023) - Fylan, Beth; Munro, James; O'Hara, Jane K.; Khatoon, Binish; Lawton, Rebecca
Abstract: Introduction: Care Opinion is an online feedback platform supporting patients to author stories about their care. It is not known whether authors would be willing to be involved in improving care through research. The aims of this study were to explore the views and preferences of Care Opinion authors about joining an online research community and to pilot new research community functionality. Methods: Five hundred and nine Care Opinion authors were invited to take part in an online survey in June 2019. Survey items included questions about participants' willingness to take part in research and their preferences for supporting processes. Data were analysed descriptively. Authors were invited to consent to join a research community and were asked to participate in three pilot studies. Results: One hundred and sixty‐three people consented to take part in the survey (32%). Participants indicated they would like to know the time commitment to the project (146, 90%), details about the organization carrying out the research (124, 76%) and safeguarding information (124, 76%). Over half indicated that they did not know how to get involved in healthcare research (87, 53%). Subsequently, 667 authors were invited to join the research community, 183 (27%) accepted, and three studies were matched to their expressed preferences for project attributes or organization type. Conclusion: Many people who leave online feedback about their experiences of healthcare are also willing to join a research community via that platform. They have strong preferences for supporting University and NHS research. Eligibility and acceptance rates to join pilot research studies varied. Further work is needed to grow the research community, increase its diversity, and create relevant and varied opportunities to support research. Patient or Public Contribution: Four members of the Safety In Numbers patient and public involvement and engagement (PPIE) group advised about survey development.